Electroencephalographic characteristics of status epilepticus after cardiac arrest. Issue 4 (April 2017) - Backman, Sofia; Westhall, Erik; Dragancea, Irina; Friberg, Hans; Rundgren, Malin; Ullén, Susann; Cronberg, Tobias
Highlights: Patterns along the ictal-interictal continuum are commonly encountered after cardiac arrest. Unequivocal and possible electrographic status epilepticus (ESE) patients have similar clinical features. Since ESE patterns appear as a continuum they should not be used in isolation for prognostication. Abstract: Objective: To describe the electrophysiological characteristics and pathophysiological significance of electrographic status epilepticus (ESE) after cardiac arrest and specifically compare patients with unequivocal ESE to patients with rhythmic or periodic borderline patterns defined as possible ESE. Methods: Retrospective cohort study of consecutive patients treated with targeted temperature management and monitored with simplified continuous EEG. Patients with ESE were identified and electrographically characterised until 72 h after ESE start using the standardised terminology of the American Clinical Neurophysiology Society. Results: ESE occurred in 41 of 127 patients and 22 fulfilled the criteria for unequivocal ESE, which typically appeared early and transiently. Three of the four survivors had unequivocal ESE, starting after rewarming from a continuous background. There were no differences between the groups of unequivocal ESE and possible ESE regarding outcome, neuron-specific enolase levels or prevalence of reported clinical convulsions. Conclusion: ESE is common after cardiac arrest. The distinction between unequivocal and possible ESE patterns was not reflected by differences in clinical features or survival. Significance: A favourable outcome is seen infrequently in patients with ESE, regardless of using strict or liberal ESE definitions.